Post-mortem examination of Hospital Inpatient COVID-19 Deaths in Lusaka, Zambia - A Descriptive Whole-body Autopsy Series. (July 2021) - Himwaze, Cordilia Maria; Telendiy, Viktor; Maate, Fred; Mupeta, Songwe; Chitalu, Chanda; Chanda, Duncan; Julius, Peter; Mumba, Chibamba; Marimo, Clemence; Hamukale, Amos; Mulenga, Llyod; Shibemba, Aaron Lunda; et al.
Highlights: Whole body autopsies define pathology of COVID-19 hospital deaths in Africa. A spectrum of pathological manifestations of COVID-19 are seen in all organs. Common findings are Pulmonary thromboembolism, Diffuse Alveolar Damage and Pneumonia. Common comorbidities of TB and HIV, in the younger age group requires further study. Abstract: Background: Since information on the pathology of COVID-19 from sub-Saharan Africa (SSA) remains scarce, the objective of our study was to define the gross pathology and histological features of COVID-19. We report data from 29 whole-body autopsies of COVID-19 deaths occurring in hospitals in Lusaka, Zambia - the first large autopsy case series from Africa. Methods: We performed a descriptive post-mortem examination study of inpatient COVID-19 related deaths at two hospitals in Lusaka, Zambia. Whole-body autopsies were conducted according to Standard Operating Procedures. Gross and histopathological examinations of all organs were performed. Patient demographics, history, co-morbidities, autopsy gross and microscopic findings, and cause(s) of death were recorded and analyzed using STATA version 14. Variables were grouped and presented as frequencies and percentages. Findings: Autopsies were performed on 29 decedents (mean age = 44 ± 15.8years; age range = 19-82; 17/29 [58.8%] males). 22/29 [75.9%] cases were <55 years of age. A spectrum of pathological manifestations of COVID-19 were seen in all organs. The commonest causes of death were pulmonary thromboembolism (13/29, 45%), Diffuse Alveolar Damage (9/29, 31%), and COVID-19 pneumonia (7/29, 25%). 22/29 (76%) had co-morbidities. Common co-morbidities included HIV (8/29, 28%), Hypertension (6/29, 20%) Tuberculosis (3/29, 10%), Diabetes (3/29, 10%). Conclusions: A spectrum of gross anatomical and histopathological findings are seen in COVID-19 deaths in hospitalized decedents. These appear broadly similar to those reported from China, Europe and USA. Differences include a younger age group, and co-morbidities of HIV and TB co-infection which require further investigation.